2002
DOI: 10.4161/cbt.86
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reproductive Hormones on Ovarian Epithelial Tumors: I. Effect

Abstract: We examined the effects of the 4 major female reproductive hormones, estradiol (E2), progesterone (P4), follicle stimulating hormone (FSH), and luteinizing hormone (LH) on thymidine incorporation in benign and malignant ovarian epithelial tumors cultured in vitro. Treatment of these tumors with E2, FSH and LH resulted in increased thymidine incorporation while treatment with P4 inhibited growth as well as thymidine incorporation. The inhibitory effect of progesterone could not be reproduced by treating the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…12 FSH, but not LH, stimulates OET cell growth by upregulating cyclin B1 expression. 13 We concluded that FSH and LH have different and often opposing roles in ovarian epithelial tumorigenesis. In addition, we have also shown that gonadotropin receptors (FSHR and LHR) are present in OSE, OEIs and a majority of OETs, including borderline tumors and OECs in peritoneal counterparts.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…12 FSH, but not LH, stimulates OET cell growth by upregulating cyclin B1 expression. 13 We concluded that FSH and LH have different and often opposing roles in ovarian epithelial tumorigenesis. In addition, we have also shown that gonadotropin receptors (FSHR and LHR) are present in OSE, OEIs and a majority of OETs, including borderline tumors and OECs in peritoneal counterparts.…”
mentioning
confidence: 87%
“…Extracted total RNA was reverse-transcribed as described previously. 14,19 Samples were incubated at 37°C for 1 hr in 20 l of 10 mM TRIS (pH 8.4), 50 mM KCl, 2 mM MgCl 2 , 1 mM DTT, 5 units of ribonuclease inhibitor, 0.5 mM dNTP, 100 pmol of oligo-d(T) [12][13][14][15][16][17][18] and 200 units of MMLV reverse transcriptase (USB, Cleveland, OH). The reaction was terminated by heating for 5 min at 95°C.…”
Section: Tissue Microdissection Rna Extraction and Reverse Transcripmentioning
confidence: 99%
“…Studies in macaques suggest an apoptotic effect of progestins on the surface of the ovary (Rodriguez et al, 1998). In vitro treatment of both benign and malignant ovarian tumour cells with progestins results in an antiproliferative response (Zhou et al, 2002).…”
mentioning
confidence: 99%
“…A recent study, however, suggested that this problem can be circumvented by co-administering progestin and estrogen (Pearce et al, 2009). Further, experiments in culture showed that progesterone reduced the proliferation of both benign and malignant ovarian tumor cells (Zhou et al, 2002). Therefore, progestin might be a key factor for preventing and suppressing ovarian cancer cell growth.…”
Section: The Role Of Sex Steroid Hormone Receptors In Cancer Therapymentioning
confidence: 99%